非关税措施国际分类 2019 - United Nations Conference on Trade; Development (United Nations, 2021)
Non-tariff measures are generally defined as policy measures other than ordinary customs tariffs that can potentially have an economic effect on international trade in goods, changing quantities traded, or prices or both. Since this definition is broad, a detailed classification is of critical importance so as to better identify and distinguish among the various forms of non-tariff measures. The classification of non-tariff measures presented here is a taxonomy of all those measures considered relevant in international trade today. It builds on an old UNCTAD classification known as the Coding System of Trade Control Measures and was developed by several international organizations forming what is called the MAST group (Multi-Agency Support Team) set up to support the Group of Eminent Persons on Non-tariff Barriers established by the Secretary General of UNCTAD in 2006. The MAST team discussed and proposed this classification, and is composed of: FAO, IMF, ITC, OECD, UNCTAD, UNIDO, World Bank and WTO. The classification is seen as evolving and should adapt to the reality of international trade and data collection needs.